2019
DOI: 10.1097/aog.0000000000003320
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Approach to Refractory Overactive Bladder and Barriers to Third-Line Therapy

Abstract: has been reviewed by the Editorial Board and by special expert referees. Although it is judged not acceptable for publication in Obstetrics & Gynecology in its present form, we would be willing to give further consideration to a revised version. If you wish to consider revising your manuscript, you will first need to study carefully the enclosed reports submitted by the referees and editors. Each point raised requires a response, by either revising your manuscript or making a clear and convincing argument as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Although this topic has been vastly understudied in the literature, one particular qualitative study interviewed patients with OAB to determine barriers to receiving third-line therapies, and identified two key barriers: lack of education about the therapies and lack of resources. 16 Poor health literacy may represent another barrier that impairs physicians' ability to foster valuable communication, and has been associated with worsened outcomes in chronic diseases. 17 Low socioeconomic status, non-native English speaking status, chronic disease, and lack of education have all been found to be associated with low health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although this topic has been vastly understudied in the literature, one particular qualitative study interviewed patients with OAB to determine barriers to receiving third-line therapies, and identified two key barriers: lack of education about the therapies and lack of resources. 16 Poor health literacy may represent another barrier that impairs physicians' ability to foster valuable communication, and has been associated with worsened outcomes in chronic diseases. 17 Low socioeconomic status, non-native English speaking status, chronic disease, and lack of education have all been found to be associated with low health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…46 Lastly, three studies have shown patients are sensitive to costs associated with third-line therapy indicating out-of-pocket cost to be an important barrier to treatment. 43,46,49 These attributes help inform SDM for OAB by bringing patient-centered concerns to the forefront of treatment decisions. It is intuitive that patients value clinical efficacy and reduction of adverse effects.…”
Section: Patient Preferences In Oab Treatment Decisionsmentioning
confidence: 99%
“…For example, one study found that while patients rank clinical efficacy of treatment highly, treatment delivery method was the most important attribute to patients with oral and transdermal treatments being favored 49 . Patients in another considered third‐line therapy to be an extreme leap rather than a natural progression to more advanced care 46 . Lastly, three studies have shown patients are sensitive to costs associated with third‐line therapy indicating out‐of‐pocket cost to be an important barrier to treatment 43,46,49 …”
Section: Patient Preferences In Oab Treatment Decisionsmentioning
confidence: 99%
“…While the authors did discuss the lack of diversity in the patient cohort, there is the potential for crowdsourcing methods to evolve with future advancements of these platforms and social media. 2 While the concept of patient-centered outcomes research is beneficial to both patients and researchers in an ideal world, using this platform to drive research brings significant limitations; baseline knowledge of etiology and treatment is not assessed, as evidenced by identification of the cause of overactive bladder being the top priority. The etiology of overactive bladder is complex and there are several proposed mechanisms that attempt to explain the pathophysiology, and with this knowledge, patients may have responded differently.…”
mentioning
confidence: 99%
“…1 Studies have identified insufficient office-education as a common modifiable barrier to additional treatment and treatment compliance for overactive bladder. 2,3 These findings suggest there is an opportunity for urologists to educate patients to better understand their condition. Furthermore, our study indicates that elucidating causes of overactive bladder is highly desired by patients.…”
mentioning
confidence: 99%